The Effect of Work Life Quality on Job Satisfaction with Organizational Support as a Mediator Variable - Azizah, Laila Nur; Erlina, Rr. (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
HR is beginning to focus more on workers' quality of life, particularly in the Islamic banking business, where service requirements and performance expectations are high. According to its Islamic goal, Bank Syariah Indonesia must create a caring environment that fosters employee health and happiness. Bank Syariah Indonesia employees in Bandar Lampung are examined for how quality of work life influences job satisfaction using perceived organizational support as a moderator. Structured surveys with five-point Likert scales yielded 130 valid responses. Data were analyzed using SEM-PLS, a partial least squares structural equation modeling approach. Data shows that work life quality boosts job satisfaction considerably. Organizational support mediates this relationship, suggesting that workers' feeling of value and employer support boost work-life balance's happiness impact. Good work-life balance, appropriate salary and benefits, competent leadership, and good job placement are all important, according to descriptive data. These findings suggest Islamic banking management should improve HR practices to promote morale and long-term productivity.